2017
DOI: 10.1007/s12265-016-9718-9
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of a Poly-l-Lactide GCSF-Functionalized Scaffold in a Model of Chronic Myocardial Infarction

Abstract: A previously developed poly-l-lactide scaffold releasing granulocyte colony-stimulating factor (PLLA/GCSF) was tested in a rabbit chronic model of myocardial infarction (MI) as a ventricular patch. Control groups were constituted by healthy, chronic MI and nonfunctionalized PLLA scaffold. PLLA-based electrospun scaffold efficiently integrated into a chronic infarcted myocardium. Functionalization of the biopolymer with GCSF led to increased fibroblast-like vimentin-positive cellular colonization and reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 69 publications
1
38
0
1
Order By: Relevance
“…Reinforced electrical conduction in scaffolds is beneficial to CM function and synchronous contraction 7 , 63 , 64 . Our results also suggest that the dopa-based conductive membranes are better for the formation of sarcomeres in CMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reinforced electrical conduction in scaffolds is beneficial to CM function and synchronous contraction 7 , 63 , 64 . Our results also suggest that the dopa-based conductive membranes are better for the formation of sarcomeres in CMs.…”
Section: Discussionmentioning
confidence: 99%
“…Engineered cardiac patches (ECP), which consist of seeding cells and scaffolds, provide promising strategies for infarcted myocardium regeneration 1 - 3 . Biomimetic microenvironments consisting of ECP can promote cardiomyocyte (CM) function and yield synchronous contraction in vitro 4 - 7 . They can also repair myocardial infarction and enhance cardiac function in vivo 6 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…They also reported neovascularization, decreased fibrosis, positive remodeling, and improved left ventricular function compared with controls . Composite of PLLA and GCF for the repair of myocardium is seen effective to induce vascularization and tissue healing . In a recent study, polypyrrole and methyl acrylic anhydride‐gelatin nanoparticles were cross‐linked on PCL membrane using mussel crosslinker to generate cardiac patch.…”
Section: Application Of Nanofiber Scaffold To Cardiac Regenerationmentioning
confidence: 97%
“…Spadaccio et al have demonstrated that functionalization of the PLLA biopolymer with granulocyte colony-stimulating factor (GCSF), tested as a ventricular patch in a rabbit chronic model of myocardial infarction, induced an angiogenetic process with a significant increase in the number of new vessels compared to the nonfunctionalized scaffold [58].…”
Section: Figure 1 Scanning Electron Microscope (Sem) Microphotographmentioning
confidence: 99%